Prevention of Power Theft and Reduction of Excessive Power Usage Using Fuzzy Logic for Residential Consumers (European Journal of Engineering Science and Technology, 2019)
This paper shows a control method to prevent users from stealing power and also to reduce excessive power usage with the assist of the fuzzy inference system. Power theft can be detected by a comparison between substation energy meter reading and the total load supplied by the electricity poles. Excessive power usage can also be detected by a comparison between the power delivered from the substation with the power consumed by the customer. The Arduino board, namely the Slave board is connected to the energy meter of each home. Another Arduino board, namely the Master board is connected to the energy meter of the substation. The Master board is used to continuously monitor the load consumption that calculated by Slave board. Any difference noticed in collected data means either power theft has occurred or excessive power usage has occurred which is legal use but may cause troubles for the power grid, such troubles may put the electricity network in the collapse condition. This difference of readings is fed as input to the Fuzzy logic control system and the corresponding change in output load is provided by the controller will be fed as input to Slave board to cutoff the electricity for preventing stealing the power and also to reduce excessive power usage. Both of Master and Slave are Arduino boards with same structure of components with different generated codes. In this paper, fuzzy logic acts as a relay in electricity theft condition and as a regulator in excessive usage condition. The simulation of both processes, including cutting off the electricity in the theft condition and regulating the amount of electricity in the extreme consumption condition, have been done by Toolbox/MATLAB using fuzzy logic controller named Mamdani. For more accurate results, simulation also has been done using another fuzzy logic controller named Sugeno Controller.